KARAKTERISTIK MEKANIK KOMPOSIT SERAT CANTULA (AGAVE CANTULA ROXB) SEBAGAI ALTERNATIF BAHAN PENGUAT TERHADAP PARTISI RUMAH - Wilaha, Lidi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Using of natural fiber as ingredients of particle board products, still have to various studies to gain the character of the product’s standard. Study of Cantula fiber utilization with matrix of Yukalac 157 BQTN-EX unsaturated polyester as the design of composite manufacturing partition (simplicity wall) of housing is professionally researched and potential, it's important to do immediately investigation potential of characteristic Cantula’s fiber as alternative composite material to partition housing. Cantula fiber that has been cleaned, then soaked with a solution of NaOH 10% for 4 hours, then recleaned back, and let it dry naturally in the room without stright sunlight for 3 days until moisture content ranged from 8-10%. The composite samples are made with combination method hand laying and press shape with the fractional volume of 10%, 20%, 30%, 40%, and 50%. For matrix and hardener, using the Polyester Yukalac Type 157 BQTN-EX and MEXPO, the formal press is made by steel. To tool test impact standard is JIS K-7113, the spesimen test use ASTM D-5941, with microphoto, and SEM cross analysis used to for failure or errors (broken) analysis. The results have overall due to the fiber volume fraction Cantula-polyester compound against mechanical characteristics is grow up experienced of toughness impact with consecutive average volume fraction 10%, 20%, 30%, 40% therefore 6831.5 J/M2, 7464.5 J/M2, 8549 J/M2 and 10151.5 J/M2. But on the fraction of the fiber volume 50% started to droppen the value until 9515 J/M2. The increasing of absorby energy is caused by adding of fiber to compound, therefore be able to increase traits of toughness or properties and reversal. The fracturing of test impact on composite Vf 10%, 20%, 30% are failure is due to the outcome of matric failure increasingly, but at Vf 40% has a strengthening of fiber that is marked with the broken fiber and matrix tend to be simultaneously. in Vf 50%. The failure of the dominant due to the composition of the matrix that is less, the reinforcement of apparent comes only from the fiber, like sawn by the cross-section, that shows the debt phenomenon of the as much as number of fibre pulled out.